A Review of Evolutionary Trends in Cloud Computing and Applications to the Healthcare Ecosystem. (20th September 2021) - Molo, Mbasa Joaquim; Badejo, Joke A.; Adetiba, Emmanuel; Nzanzu, Vingi Patrick; Noma-Osaghae, Etinosa; Oguntosin, Victoria; Baraka, Mushage Olivier; Takenga, Claude; Suraju, Sadeeq; Adebiyi, Ezekiel F.
Abstract : Cloud computing is a technology that allows dynamic and flexible computing capability and storage through on-demand delivery and pay-as-you-go services over the Internet. This technology has brought significant advances in the Information Technology (IT) domain. In the last few years, the evolution of cloud computing has led to the development of new technologies such as cloud federation, edge computing, and fog computing. However, with the development of Internet of Things (IoT), several challenges have emerged with these new technologies. Therefore, this paper discusses each of the emerging cloud-based technologies, as well as their architectures, opportunities, and challenges. We present how cloud computing evolved from one paradigm to another through the interplay of benefits such as improvement in computational resources through the combination of the strengths of various Cloud Service Providers (CSPs), decrease in latency, improvement in bandwidth, and so on. Furthermore, the paper highlights the application of different cloud paradigms in the healthcare ecosystem.